2004
DOI: 10.1029/2004jc002428
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the thin ice thickness and heat flux for the Chukchi Sea Alaskan coast polynya from Special Sensor Microwave/Imager data, 1990–2001

Abstract: [1] One of the largest Arctic polynyas occurs along the Alaskan coast of the Chukchi Sea between Cape Lisburne and Point Barrow. For this polynya, a new thin ice thickness algorithm is described that uses the ratio of the vertically and horizontally polarized Special Sensor Microwave/Imager (SSM/I) 37-GHz channels to retrieve the distribution of thicknesses and heat fluxes at a 25-km resolution. Comparison with clear-sky advanced very high resolution radiometer data shows that the SSM/I thicknesses and heat fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
180
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(193 citation statements)
references
References 20 publications
9
180
1
Order By: Relevance
“…For ice thickness between 0.2-0.4 m, the sensible heat flux may be as large as 100 W m . This was also confirmed by satellite-derived data for ice thickness and sensible heat flux for Arctic polynyas [53]. Impacts of refreezing leads in terms of enhanced sensible and latent heat fluxes and a decrease in atmospheric stability were reported downwind of the lead up to 60 m altitude [48].…”
Section: Meteorologysupporting
confidence: 58%
“…For ice thickness between 0.2-0.4 m, the sensible heat flux may be as large as 100 W m . This was also confirmed by satellite-derived data for ice thickness and sensible heat flux for Arctic polynyas [53]. Impacts of refreezing leads in terms of enhanced sensible and latent heat fluxes and a decrease in atmospheric stability were reported downwind of the lead up to 60 m altitude [48].…”
Section: Meteorologysupporting
confidence: 58%
“…Pacific Winter Water, centered near S = 33.1, has long been recognized as primary component of the western Arctic halocline [Coachman et al, 1975]. Pacific Winter Water through the Bering Strait [Woodgate and Aagaard, 2005] was modified in the coastal polynya between Point Barrow and Cape Lisburne (e.g., increased salinity due to ice formation) [Cavalieri and Martin, 1994;Weingartner et al, 1998;Martin et al, 2004]. However, the spatial distribution of this more saline water in the Canada Basin and its role in the formation of basin-scale oceanic structures has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Kern et al 2006) revealed that active and passive microwave data are useful mainly through the thermodynamic processes that control both ice thickness and surface dielectric properties. Based on these results, the thickness algorithms for coastal polynyas in Arctic and Antarctic regions, combined with NOAA/AVHRR data were also developed (Martin et al 2004;Tamura et al 2007). For perennial ice, the measurement of the freeboard depth has been proved to be effective with the assumption of isostatic balance, from field observations in the Arctic (Comiso et al 1991;Wadhams et al 1992) and from satellite altimetry (Laxon et al 2003;Kwok et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Based on these results, the thickness algorithms for coastal polynyas in Arctic and Antarctic regions, combined with NOAA/AVHRR data were also developed (Martin et al 2004;Tamura et al 2007). For perennial ice, the measurement of the freeboard depth has been proved to be effective with the assumption of isostatic balance, from field observations in the Arctic (Comiso et al 1991;Wadhams et al 1992) and from satellite altimetry (Laxon et al 2003;Kwok et al 2004). While the algorithm for stable thin ice or thick perennial ice has been explored, relatively thick sea ice in SIZ remains a big issue.…”
Section: Introductionmentioning
confidence: 99%